Peran Perempuan dalam Komunitas Aboge di Kedungbanteng Blitar - Ramlan, Roni; Nurapipah, Laela (IAIN Tulungagung, 2019)
This research used qualitative with ethnographic approach and, the data analyze using socio-feminist. Ethnographic methods included in the qualitative research method, which is to see about the natural behavior of an entire culture or social community. While, feminism are used to see the existence of thewoman role in a community. The data collection technique was obtained from interviews, observation, documentation and review of the literature. Based on the results of this study it can be concluded that (1) in the social structure of the Aboge community, they are very willed the equality between men and women. Women have an important role and position of which is almost the same as the men. The woman recognized for his role as the first educator for her children. In addition, women also play a main role as the economy supporterin increasing family prosperity, and joined in many kinds of activities actively. as well as religious ritual ceremonies. In the tradition of Aboge community, a spiritualist in increasing spirituality always do things that still relates to mystical. Unfortunately, the stereotype of women as being given to someone who is gentle and does not speak harshly is often at odds with the concept of power (spiritualist) which includes stubbornness, strength and might. This effect on women's participation are being restricted and caused the loss of female spiritualist figures. (2) Women in the Aboge community experience some form of discrimination in the form of double burden, marginalization, subordination, and real stereotypes without realizing it is an act of perpetuating power in attendance because women have no bargaining position.